KEUANGAN ANALISIS RASIO PROFITABILITAS DAN RASIO SOLVABILITAS DI PT INDOFOD SUKSES MAKMUR TBK TAHUN 2016-2017: ANALISIS RASIO PROFITABILITAS DAN RASIO SOLVABILITAS DI PT INDOFOD SUKSES MAKMUR TBK TAHUN 2016-2017 - Budisokhi Ndruru (Fakultas Ekonomi Prodi Akuntansi, 2022)
ANALYSIS OF PROFITABILITY RATIO AND SOLVENCY RATIO AT PT INDOFOOD SUKSES MAKMUR TBK IN 2016-2017 PT Indofood Sukses MakmurTbk, is one of the leading instant noodle and processed food companies in Indonesia. One of the ways used to maintain the financial stability of a company is by conducting an analysis and evaluation of the company which later the analysis will maximize relatively little information into broad and accurate information.To find out the financial statements of a company requires analysis and financial ratios. The purpose of this research is to find out the state of financial statements through the financial ratio of its indicative, at PT Indofood SuksesMakmurTbk in 2016 to 2017.The method carried out by researchers is a method of analyzing the ratio of profitability and solvency. The results of this study showed that in 2016 to 2017 PT Indofood Sukses Makmur Tbk was classified as a fairly healthy company because the ratio level was norm